Spit it out: Is caffeine mouth rinse an effective ergogenic aid? A systematic review and meta-analysis - Nabuco, L. L.; Mendes, G. F.; Barreto, G.; Saunders, B.; Reis, C. E. G. (Strength and Conditioning Journal, 2023)
The effects of caffeine mouth rinse (Caff-MR) on sports performance have been evaluated by recent studies presenting contrasting results. Therefore, this systematic review aimed to summarize the evidence regarding the effects of Caff-MR on sports performance. According to Preferred Reporting Items for Systematic Reviews and Meta-Analyses recommendations, the search through PubMed, Web of Science, and Scopus databases was performed until December 2021. A random-effects meta-analysis of standardized mean differences was performed to assess the overall effect of Caff-MR on sports performance-related outcomes. Sixteen studies met the inclusion criteria (207 participants). The meta-analysis showed no significant overall effect of Caff-MR on sports performance (p = 0.09). Moreover, no effects were shown on maximal heart rate or ratings of perceived exertion. The risk of bias for the included studies assessed using the risk of bias in randomized trials Cochrane tool presented 87.5% (n = 14) of the studies as medium and 12.5% (n = 2) as high scores. These data do not support using Caff-MR for sports performance, although more consistent and well-controlled studies are warranted. Large heterogeneity in study designs precludes making practical recommendations for exercise performance. More research is warranted to elucidate the potential of Caff-MR, specifically focusing on determining the optimal dose.